Relevance of NADH Dehydrogenase and Alternative Two-Enzyme Systems for Growth of Corynebacterium glutamicum With Glucose, Lactate, and Acetate - Maeda, Tomoya; Koch-Koerfges, Abigail; Bott, Michael (Frontiers in Bioengineering and Biotechnology, 2021)
The oxidation of NADH with the concomitant reduction of a quinone is a crucial step in the metabolism of respiring cells. In this study, we analyzed the relevance of three different NADH oxidation systems in the actinobacterial model organism Corynebacterium glutamicum by characterizing defined mutants lacking the non-proton-pumping NADH dehydrogenase Ndh (ndh) and/or one of the alternative NADH-oxidizing enzymes, L-lactate dehydrogenase LdhA (ldhA) and malate dehydrogenase Mdh (mdh). Together with the menaquinone-dependent L-lactate dehydrogenase LldD and malate:quinone oxidoreductase Mqo, the LdhA-LldD and Mdh-Mqo couples can functionally replace Ndh activity. In glucose minimal medium the ndh mutant, but not the ldhA and mdh strains, showed reduced growth and a lowered NAD+/NADH ratio, in line with Ndh being the major enzyme for NADH oxidation. Growth of the double mutants ndhmdh and ndhldhA, but not of strain mdhldhA, in glucose medium was stronger impaired than that of the ndh mutant, supporting an active role of the alternative Mdh-Mqo and LdhA-LldD systems in NADH oxidation and menaquinone reduction. In L-lactate minimal medium the ndh mutant grew better than the wild type, probably due to a higher activity of the menaquinone-dependent L-lactate dehydrogenase LldD. The ndhmdh mutant failed to grow in L-lactate medium and acetate medium. Growth with L-lactate could be restored by additional deletion of sugR, suggesting that ldhA repression by the transcriptional regulator SugR prevented growth on L-lactate medium. Attempts to construct a ndhmdhldhA triple mutant were not successful, suggesting that Ndh, Mdh and LdhA cannot be replaced by other NADH-oxidizing enzymes in C. glutamicum.